The Embodied Female. - Alizade, Alcira (Psychoanalysis & women series., 2002)
This is the first volume in a unique series arising out of the Committee on Women and Psychoanalysis. This volume presents a collection of highly original and insightful essays broadly concerned with the study of the psychic corollaries of women's physical experience.